Digging deeper: Understanding the contribution of subsoil carbon for climate mitigation, a case study of Ireland. Issue 98 (August 2019) - Simo, I.; Schulte, R.; O'Sullivan, L.; Creamer, R.
Highlights: SOC stock calculations must measure SOC concentrations at least to 50 cm. Subsoil SOC provides an important contribution to carbon storage in soils. Current national inventory reporting do not consider the SOC in the deeper layers. Further research is needed to understand the storage mechanism of SOC in subsoils. Abstract: In an attempt to counter the progress of climate change, the European Commission 2030 climate and energy framework developed a binding target to cut GHG emissions within the territory by at least 40% below 1990 levels, by 2030. In the past, this did not include the role of soils in providing a sink for carbon. As of 2014, the European Commission legislative proposed to integrate greenhouse gas emissions and removals from LULUCF in the 2030 climate and energy framework, allowing for the contribution of carbon sinks in national inventories. To calculate the potential of these sinks it is essential to firstly understand what stocks exist at a national scale and identify the so-called 'carbon hotspots' in the landscape to reduce the potential leaks in the system. This is further enhanced by identifying soils which provide the potential for further sequestration of carbon, due to their soil texture and aggregate composition. Moreover, deeper soil horizons may have a high capacity to sequester significant amounts of SOC as the turnover time and chemical recalcitrance of soil organic matter (SOM) increases with depth (Lorenz and Lal, 2005 ). This study highlights the need to dig deeper and assess soil carbon stocks below the standard 30 cm depth, applied in many calculations and models, in order to derive sufficiently accurate estimations of soil organic carbon (SOC) stocks and the total quantity of stable SOC at depth. Using Ireland as a case study, SOC stock maps are produced with the objective of identifying and securing existing information for SOC and to show the spatial distribution and geographical variation of SOC stock at different depths. Using empirical data from a national soil survey, SOC measurements from the surface 30 cm, 50 cm and 1 m were compared across all soil types. The results indicate a large variation between soils when comparing the SOC of the first 30 cm only, while the proportion of total SOC stock contained within 0–50 cm was more consistent within subgroups of soil types, and accounts for 90% of the carbon found to 1 m. Luvisols and Stagnosols have been previously identified as soils capable of sequestering larger stores of SOC in their subsoils. These soil types were spatially mapped and the stock converted to CO2 emission equivalents. On average, up to 40 t ha −1 of stable SOC is contained at a depth below 30 cm. At national level, this adds up to 69 Mt of SOC. This research provides a spatially targeted approach that combines efforts to reduce CO2 emissions from carbon hotspots while also augmenting the sequestration of stable carbon at depth in soils with clay illuviation and wetness (stagnic) diagnostic horizons.